Peasants in history - Hosbawm, E. J. (ed.) (Bombay, 1980)
This volume in memory of Daniel Thorner brings together eighteen essays by a number of his colleagues, admirers and friends. Daniel Thorner was in the first instance a student of India, particularly of problems of rural transformation in India. The largest single group of contributions therefore concerns agrarian issues in the sub-continent. Thorner was however far from a narrow regional specialist; he visualized the problems of economic development as of peasant agriculture. During the last decades of his life, he emerged as a major analyst of peasant economy in general and its historical processes in differerent countries. The papers collected here, the editors believe, will demonstrate the degree of debt owed to him by both students of agrarian problems and economic historians.
Keywords: Peasantry